Change management in different phases of IS project lifecycle - Hansen, Aura (My University, 2023)
The role of change has become more crucial over the past few decades. To keep up with the competition, organisations have to find ways to respond to the changing world, and at the same time, improve their efficiency and competitiveness. (Ziemba & Oblak 2015.) Furthermore, the usage of IT equipment and information systems has increased, and they have become a necessity (Chen et. al. 2010, 1). According to Henderson & Venkatraman (1993), IT has changed from an invisible support and enabler of operations to a strategic success factor, and it can be said that IT transformations are important strategic changes. Vast amounts of resources are thus spent on them, but the outcomes of these projects are uncertain, and the failure rates are high (Stoica & Brouse 2013, 728). In fact, information system projects fail more often than they succeed (Stoica & Brouse 2013, 728), and, according to a study by McKinsey & Company (2019), 70 per cent of all enterprise technology transformations fail. The information system projects are usually managed by project management models, such as project lifecycle model (Pereira, Varajão & Takagi 2022; Skulmoski & Hartman, 2010). Change management is not represented in them (Ziemba & Oblak 2015) although it has significant influence in the success of organisational change projects (Gilley et al. 2008; Jones et al. 2005; Turner & Müller, 2005). Interestingly, change management and project management are topics that have been studied broadly, but there is still limited research that combines the two (Ziemba & Oblak 2015). According to Hornstein (2014), organisations should broaden their knowledge of change management in order to recognize its necessity and significance to project success. Therefore, this study aims to find out how change management can be used to carry out IS projects and what are the best practices for change management in each phase of an IS project lifecycle. In this thesis, different organisational change management models and theories are introduced and then compared to empiric evidence from six change management professionals who have extensive experience of managing organizational changes in IS projects. By analysing the interview data with the help of the Gioia method, a framework that combines the IS project lifecycle phases and change management actions in each phase, has been composed. Based on the results it can be concluded that in the first phase of the IS project lifecycle, it is crucial to create a project team and build trust, bring the people perspective right from the beginning, create a high-level analysis of the upcoming change, define the project scope, create a clear vision and objective for the change and assure that the top management supports the change. In the second phase, a stakeholder analysis and a change management plan should be made as well as evaluating the gap between where the organisation is now and where it would like to be. It is also important to define whether the focus should be on configurating the system or the processes. In the third phase, attention should be paid on change impact assessments, employees involvement, change readiness analysis, communication, creating a sense of urgency, training, pedagogically competent trainer, and hypercare. And finally, in the fourth phase of the IS project lifecycle, risk identification, supporting the organisation and performance measurement are important change management actions.

Muutoksen merkitys on korostunut viime vuosikymmeninä. Pysyäkseen kilpailussa mukana organisaatioiden on löydettävä keinoja vastata muuttuvaan maailmaan ja samalla parannettava tehokkuuttaan ja kilpailukykyään (Ziemba & Oblak 2015). Lisäksi tietotekniikan ja tietojärjestelmien käyttö on lisääntynyt, ja niistä on tullut välttämättömyys (Chen et. al. 2010, 1). Hendersonin ja Venkatramanin (1993) mukaan tietotekniikan rooli on muuttunut toiminnan näkymättömästä tuesta ja mahdollistajasta strategiseksi menestystekijäksi, ja voidaankin sanoa, että IT-muutokset ovat tärkeitä strategisia muutoksia. Niihin käytetään valtavia määriä resursseja, mutta näiden hankkeiden tulokset ovat kuitenkin epävarmoja ja epäonnistumisprosentit ovat korkeita (Stoica & Brouse 2013, 728). Itse asiassa tietojärjestelmähankkeet epäonnistuvat useammin kuin ne onnistuvat (Stoica & Brouse 2013, 728), ja McKinsey & Companyn (2019) tutkimuksen mukaan 70 prosenttia kaikista IT-muutoksista epäonnistuu. Tietojärjestelmäprojekteja johdetaan yleensä projektinhallintamalleilla, kuten projektin elinkaarimallilla (Pereira, V arajão & Takagi 2022; Skulmoski & Hartman, 2010). Muutosjohtaminen ei ole niissä edustettuna (Ziemba & Oblak 2015), vaikka sillä onkin merkittävä vaikutus organisaatiomuutosten onnistumiseen (Gilley et al. 2008; Jones et al. 2005; Turner & Müller, 2005). Mielenkiintoista on, että muutosjohtaminen ja projektijohtaminen ovat aiheita, joita on tutkittu laajasti, mutta näitä kahta yhdistäviä tutkimuksia on vielä vähän (Ziemba & Oblak 2015). Hornsteinin (2014) mukaan organisaatioiden tulisi laajentaa tietämystään muutosjohtamisesta, jotta ne tunnistaisivat sen tarpeellisuuden ja merkityksen projektin onnistumiselle. Tämän vuoksi tässä tutkimuksessa pyritään selvittämään, miten muutosjohtamista voidaan hyödyntää tietojärjestelmäprojektien toteuttamisessa, ja mitkä ovat parhaita käytäntöjä muutosjohtamiselle tietojärjestelmäprojektien elinkaaren kussakin vaiheessa. Tässä tutkielmassa esitellään erilaisia muutosjohtamisen teorioita ja malleja, joita sitten verrataan empiiriseen aineistoon, joka on saatu kuudelta muutosjohtamisen ammattilaiselta, joilla on runsaasti kokemusta tietojärjestelmäprojektien muutosjohtamisesta. Haastatteluaineistoa analysoidaan Gioia-menetelmän avulla, ja tulosten pohjalta muodostetaan viitekehys, jossa yhdistetään tietojärjestelmäprojektin elinkaaren vaiheet ja muutosjohtamisen toimenpiteet kussakin vaiheessa. Tulosten perusteella voidaan päätellä, että tietojärjestelmäprojektien elinkaaren ensimmäisessä vaiheessa on ratkaisevan tärkeää perustaa projektitiimi, rakentaa luottamusta, ottaa ihmisnäkökulma huomioon heti alusta alkaen, laatia korkean tason analyysi tulevasta muutoksesta, määritellä hankkeen laajuus, luoda selkeä visio ja tavoite muutokselle sekä varmistaa, että ylin johto tukee muutosta. Toisessa vaiheessa olisi laadittava sidosryhmäanalyysi ja muutoksenhallintasuunnitelma sekä arvioitava kuilu organisaation nykyisen tilan ja sen tilan välillä, jota organisaatio tavoittelee. On myös tärkeää määritellä, pitäisikö keskittyä järjestelmän vai prosessien konfigurointiin. Kolmannessa vaiheessa olisi kiinnitettävä huomiota muutoksen vaikutusten arviointiin, työntekijöiden osallistumiseen, muutosvalmiusanalyysiin, viestintään, kiireellisyyden tunteen luomiseen, koulutukseen, pedagogisesti pätevään kouluttajaan ja hypercare-vaiheeseen. Elinkaaren viimeisessä vaiheessa riskien tunnistaminen, organisaation tukeminen ja suorituskyvyn mittaaminen ovat tärkeitä muutosjohtamisen toimenpiteitä.
Keywords: change management, IS project lifecycle, organizational change, information systems, change adoption